Public knowledge and attitudes towards wastewater treatment works and plastic pollution in the Vhembe District Municipality, South Africa - Khumbelo Mabadahanye; Mwazvita T.B. Dalu; Farai Dondofema; Linton F. Munyai; Tatenda Dalu (PLoS ONE, 2025)
Concerns about plastic pollution and wastewater treatment plants (WWTPs) have grown in communities near these facilities due to their negative effects on the local environment and public health. This study surveyed 150 community members in the municipality of Thulamela local municipality (TLM) in the Vhembe district municipality (VDM), and the data was analysed using Microsoft Excel and SPSS. Female participants (57.3%) comprised a larger proportion than male participants (41.3%), and employed participants (32.0%) were more represented than retired ones (4.6%). Sixty–one percent (61%) of participants knew WWTPs, while 39% were not. Forty–eight percent expressed concerns about WWTPs due to odours, health risks, and property value loss due to the proximity to the plants. Seventy–seven percent of participants reported being aware of plastic pollution in wastewater, while 54% indicated receiving information about this issue. Spearman’s rank–order correlation analysis revealed significant relationships among variables (sociodemographic and environmental consciousness behaviour), with higher education levels negatively correlated with WWTP awareness, while awareness of WWTPs positively correlated with knowledge of plastic pollution. Participants showed interest in educational outreach and gaining more information about WWTPs and plastic pollution. Public education and awareness campaigns are essential to address community concerns and increase environmental awareness.